Penerapan Model Spiritual Leadership terhadap Peningkatan Kinerja Perawat - Hartati, Theresia; Bunga, Asnet Leo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to see how implementing the spiritual leadership model improves nurse performance. The research method used is a literature review through electronic databases and websites, namely Google Scholar, Science Direct, PubMed, and Semantic Scholar, with inclusion criteria including ten journals with the keywords